Controlled trial to evaluate protection of high-risk infants against respiratory syncytial virus disease by using standard intravenous immune globulin. - Meissner, H C (1993)
We performed a randomized, controlled trial of intravenous immune globulin (respiratory syncytial virus [RSV] neutralizing [Nt] antibody titer of 1:950 in 5% solution) to evaluate protection against RSV-induced disease over two respiratory virus seasons. Forty-nine children (mean age at enrollment, 4.5 months) with severe congenital heart disease or bronchopulmonary dysplasia were randomized as follows. Twenty-four patients were followed as controls and received no immune globulin. Twenty-five patients received monthly infusions of immune globulin at a dose of 500 mg/kg of body weight. There was a similar distribution between groups of patients with heart disease and bronchopulmonary dysplasia. There were 12 culture-proven RSV infections, 6 in the prophylaxis group and 6 in the control group. There was a trend toward less severe RSV illness in immune globulin recipients, as measured by length of hospitalization. Four of the six immune globulin recipients were hospitalized for a total of 35 days (mean, 8.8 +/- 5.0 days) because of RSV illness, in contrast to 51 hospital days (mean, 12.8 +/- 7.6 days) among RSV-infected controls. We conclude that monthly infusions of standard immune globulin containing RSV Nt antibodies may be safely administered to high-risk children, but that standard intravenous immune globulin does not contain sufficient RSV Nt antibody titer to fully protect against severe RSV illness.